2013
DOI: 10.1039/c3tb20285b
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser fragmentation from water-dispersed microcolloids: toward fast controllable growth of ultrapure Si-based nanomaterials for biological applications

Abstract: International audienceAn ultrashort laser-assisted method for fast production of concentrated aqueous solutions of ultrapure Si-based colloidal nanoparticles is reported. The method profits from the 3D geometry of femtosecond laser ablation of water-dispersed microscale colloids, prepared preliminarily by the mechanical milling of a Si wafer, in order to avoid strong concentration gradients in the ablated material and provide similar conditions of nanocluster growth within a relatively large laser caustics vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 51 publications
2
79
0
4
Order By: Relevance
“…For this pulsed laser fragmentation (PLFL) technique usually a pulsed laser beam is focused into a suspension with microand/or nanoparticles to reach the necessary fluences and intensities for sufficient fragmentation. Earlier and recent investigations were focusing on metallic particles [10][11][12][13][14][15][16], whereby studies are more and more including PLFL of alloy particles [17,18], semiconductors and organic particulate materials [19][20][21][22][23][24]. This particle comminution method of pulsed laser fragmentation in liquids (PLFL) could potentially further enhance nanoparticle productivity [20,25], but modelling and mass balance becomes more complex compared to PLAL, because of the fabricated product mixing with the educt particles.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For this pulsed laser fragmentation (PLFL) technique usually a pulsed laser beam is focused into a suspension with microand/or nanoparticles to reach the necessary fluences and intensities for sufficient fragmentation. Earlier and recent investigations were focusing on metallic particles [10][11][12][13][14][15][16], whereby studies are more and more including PLFL of alloy particles [17,18], semiconductors and organic particulate materials [19][20][21][22][23][24]. This particle comminution method of pulsed laser fragmentation in liquids (PLFL) could potentially further enhance nanoparticle productivity [20,25], but modelling and mass balance becomes more complex compared to PLAL, because of the fabricated product mixing with the educt particles.…”
Section: Introductionmentioning
confidence: 98%
“…Yan et al reported structures resulting from sintering (melting) and fragmentation occurring by postirradiation subsequent to material ablation from a solid target [30] indicating that both, ablation and melting fluence regimes, responsible for forming these structures may occur in the same vessel because of the fluence gradients. One possibility is to irradiate highly concentrated particle suspension [20] to reduce the penetration depth of the laser beam into the liquid and thereby minimize the fluence gradient. But this will make long irradiation times necessary to fragment an adequate amount of particles and at the same time drastically increases the particle-particle interactions.…”
Section: Introductionmentioning
confidence: 99%
“…2a, the electrochemically-prepared PSi NPs have a wide dispersion in size and shape: the size distribution contains a broad spectrum with the peak value at about 50 nm and a considerable portion of larger (several hundreds of nm) NPs. Second, we used Si-based NPs prepared by methods of femtosecond laser ablation in deionized water212223 (see details in the Methods section). The latter laser-ablative approach is unique in avoiding any residual contamination of the NP surface as a result of the synthesis in a clean aqueous environment in the absence of any toxic by-products.…”
mentioning
confidence: 99%
“…This feature, surprising for a not highly emissive bulk material, has attracted a wide interest motivated by the use in several application fields (optoelectronics, photovoltaics, bioimaging) [2][3][4][5], and has led the research towards the development of production methods able to finely control the physical and chemical properties of the nanostructured Si. To this purpose, laser ablation (LA) in liquids is particularly promising since it provides effective control parameters (laser photon energy, fluence, pulse duration, liquid reactivity) for the morphology and the structure of related products and, therefore, it has attracted much attention [6][7][8][9][10]. Previous works have demonstrated the viability of a green method to produce Si-nanocrystals (Si-NCs) by LA in water, and have addressed their luminescence properties [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%